2019
DOI: 10.1248/cpb.c18-00725
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Medicinal Product and Dietary Supplements Containing <i>Vitex agnus-castus</i> by HPLC Fingerprint and Quantitative Analyses

Abstract: In this study, we aimed to evaluate the quality of 11 products sold in Japan (one medicinal product and 10 dietary supplements) containing/claiming to contain chasteberry extract (fruit of Vitex agnus-castus L.) using HPLC fingerprint (15 characteristic peaks), quantitative determination of chemical marker compounds, and a disintegration test. The HPLC profile of the medicinal product was similar to that of the reference standard of V. agnus-castus fruit dry extract obtained from European Directive for the Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
(20 reference statements)
0
7
1
2
Order By: Relevance
“…Moreover, the chemical analysis by HPLC-MS was identified 11 types of flavonoids; the most abundant is luteolin with high levels especially in the flower part with a value of 77047:5 ± 4006:47 μg/kg. Importantly, other previous studies have also revealed numerous phenolic compounds in V. agnus castus extracts [6,[19][20][21]. Indeed, the rate of phenolic compounds found in our results is not exactly similar to those identified in these reposted works.…”
Section: Resultscontrasting
confidence: 93%
“…Moreover, the chemical analysis by HPLC-MS was identified 11 types of flavonoids; the most abundant is luteolin with high levels especially in the flower part with a value of 77047:5 ± 4006:47 μg/kg. Importantly, other previous studies have also revealed numerous phenolic compounds in V. agnus castus extracts [6,[19][20][21]. Indeed, the rate of phenolic compounds found in our results is not exactly similar to those identified in these reposted works.…”
Section: Resultscontrasting
confidence: 93%
“…To overcome this gap, patient and healthcare education should be facilitated to provide safe recommendations for VAC use [ 6 ]. Besides, the effects may be influenced by the cultivation region differences in soil, weather, and altitude, the quality of the active prepared herb, and the incorrect or poor quality manufacturing process [ 28 ]. In addition, the type of the nanobarrier used in the VAC extract could potentially impact the oral bioavailability of the drug [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dominant flavonoids are casticin and luteolin-7-glycoside. The other compounds present are luteolin , 3,3′-dihydroxy-5,6,7,4′-tetramethoxyflavone, 3,7-dimethylquercetin, 3-O-methylkaempferol, 3-hydroxy-5,6,7,4-tetramethoxyflavone, 3-methylquercetin, 3-methylkaempferol, 5,3′,5′-trihydroxymethoxyflavanone, 5,7,3′,5′-tetrahydroxyflavanone, apigenin, artemetin, vitexin, orientin, isovitexin, isoorientin, kaempferol, penduletin, and eupatorin (Chen et al, 2011;Choudhary et al, 2009;Hajdú et al, 2007;Makhmoor and Choudhary, 2010;Mari et al, 2015;Sogame et al, 2019;Sorensen and Katsiotis, 1999).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Some other compounds with phenolic structure have been identified. These are 3,4-dihydroxybenzoic acid, 5-hydroxy-2-methoxybenzoic acid, vanillic acid, caffeic acid, ferulic acid, p-hydroxybenzoic acid, p-hydroxyphenylethanol-p-coumarate, myzodendrone, chlorogenic acid, methylisovanillate, and methyl 3,4-dihydroxybenzoate (Chen et al, 2011;Choudhary et al, 2009;Kuruüzüm-Uz et al, 2003;Li et al, 2013;Makhmoor and Choudhary, 2010;Şarer et al, 2008;Sogame et al, 2019).…”
Section: Chemical Compositionmentioning
confidence: 99%